2011
DOI: 10.1007/978-3-642-24100-0_9
|View full text |Cite
|
Sign up to set email alerts
|

SMV: Selective Multi-Versioning STM

Abstract: We present Selective Multi-Versioning (SMV), a new STM that reduces the number of aborts, especially those of long read-only transactions. SMV keeps old object versions as long as they might be useful for some transaction to read. It is able to do so while still allowing reading transactions to be invisible by relying on automatic garbage collection to dispose of obsolete versions.SMV is most suitable for read-dominated workloads, for which it achieves much better performance than previous solutions. It has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…JVSTM [3,4] and SMV [17] never reclaim versions that may still be needed, but an active writer may create an unbounded number of history nodes for a reader to traverse. Systems that revert to inevitability for long-running readers are of course fundamentally blocking: a reader cannot start until active writers get out of the way.…”
Section: Theorem 2 the Total Space Ts Consumed By History Lists Is Imentioning
confidence: 99%
See 1 more Smart Citation
“…JVSTM [3,4] and SMV [17] never reclaim versions that may still be needed, but an active writer may create an unbounded number of history nodes for a reader to traverse. Systems that revert to inevitability for long-running readers are of course fundamentally blocking: a reader cannot start until active writers get out of the way.…”
Section: Theorem 2 the Total Space Ts Consumed By History Lists Is Imentioning
confidence: 99%
“…More recently, Perelman et al demonstrated, in their SMV system [17], how to eliminate explicit deletion: they distinguish between hard and weak references to an object version v, and arrange for the last hard reference to become unreachable once no running transaction has a start time earlier than that of the transaction that overwrote v.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach for garbage collection was presented in our selective multi-versioning (SMV) STM [15]. SMV keeps a variable number of old versions, which reduces memory usage while ensuring read-only transactions can always commit.…”
Section: Space Optimalitymentioning
confidence: 99%
“…This optimistic approach inevitably leads to aborting transactions in some cases, such as when data dependencies introduce inconsistencies. When many transactions contend on the same data objects, aborts may become frequent, causing a devastating effect on performance [2,15]. Therefore, reducing the number of aborts is an important challenge for STMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation